HLA typing by sequence-specific primers - Bunce, Michael; Passey, B. (Humana Press, 2013)
HLA typing by sequence-specific primers (PCR-SSP) is a commonly used technique in HLA typing in which multiple pairs of cis-located allele-specific primers are used to determine the alleles present in a given DNA sample. Although the technique is around two decades old, it still offers a relatively straight forward way of typing and has the benefit of using commonly available laboratory equipment. Here we describe the background of the PCR-SSP, how to design and validate reactions, and common problems that arise. © Springer Science+Business Media, LLC 2013.